1989
DOI: 10.1002/bit.260330106
|View full text |Cite
|
Sign up to set email alerts
|

Anoxic–oxic activated‐sludge of cyanides and phenols

Abstract: The anoxic-oxic activated-sludge process has been evaluated in a laboratory investigation as a means for effective treatment of cyanide-laden wastewaters, with phenols used as the organic carbon sources for denitrification reactions. The performance of the process was evaluated at different levels of feed cyanide concentration and mean cell residence time (MCRT). The results obtained indicate that the phenolic compounds used can be effectively used as the organic carbon sources to promote denitrification react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

1991
1991
2009
2009

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…6, the concentration of NH 4 + -N in the effluent is usually greater than that of the influent. This is due to the presence of organic nitrogen and thiocyanate in the influent, since the former is transformed into NH 4 + during the process of biodegradation and the latter into NH 4 + , CO 2 and SO 4 2− [16,17,20]. This behaviour was confirmed by means of respirometric assays employing synthetic water containing SCN − and not NH 4 + ; it being observed that the biodegradation of the thiocyanate gave rise to the generation of ammonia.…”
Section: Study Of the Biodegradation Of Coke Wastewater Without The Amentioning
confidence: 60%
See 1 more Smart Citation
“…6, the concentration of NH 4 + -N in the effluent is usually greater than that of the influent. This is due to the presence of organic nitrogen and thiocyanate in the influent, since the former is transformed into NH 4 + during the process of biodegradation and the latter into NH 4 + , CO 2 and SO 4 2− [16,17,20]. This behaviour was confirmed by means of respirometric assays employing synthetic water containing SCN − and not NH 4 + ; it being observed that the biodegradation of the thiocyanate gave rise to the generation of ammonia.…”
Section: Study Of the Biodegradation Of Coke Wastewater Without The Amentioning
confidence: 60%
“…The experimental data were fitted to an exponential curve (r = 0.982) which suggests that from 75 h on no higher removal than 65.6% would be achieved, even by increasing the HRT. Nitrification does not take place using HRT below 12 over SCN − biodegradation, resulting in low removal efficiency [16][17][18]. In this case, the concentration of NH 4 + -N in the influent was both very high and variable (ranging from 506 to 1108 mg/L) due to certain problems in the prior stripping treatment carried out at the steelworks.…”
Section: Study Of the Biodegradation Of Coke Wastewater With The Addimentioning
confidence: 97%
“…Fortunately, free cyanide below 0.1 mg/L flowed into nitrification process of full-scale cokes wastewater treatment facility owing to its anaerobic degradation under denitrification condition (Table 1). According to a report of Richards and Shieh [24], free cyanide can be removed to some degree by anaerobic bacteria. Therefore, there was less possibility of incomplete nitrification by toxic effect of free cyanide under normal condition, but an abnormal influx of free cyanide into nitrification process may cause an irrecoverable damage to nitrifying bacteria.…”
Section: Effect Of Cyanide Compounds On Nitrificationmentioning
confidence: 97%
“…The wastewater consists of ammonia, cyanide, thiocyanate, sulfides, and a wide variety of complex hydrocarbons such as phenolics, polynuclear aromatic hydrocarbons, and various heterocyclic compounds [3,4]. Most of the chemical oxygen demand (COD) originates from phenol, which is a toxic inhibitory substrate but is also a useful carbon source for acclimatized microorganisms [5]. Cyanide is a highly toxic organic compound even at low concentrations and its presence in aqueous media is severely restricted by regulations [6,7].…”
Section: Introductionmentioning
confidence: 99%